INTERACTIONS BETWEEN AUTONOMOUS VEHICLES, CYCLISTS, AND PEDESTRIANS FROM THE PERSPECTIVE OF POTENTIAL USERS AND NON-USERS OF AUTONOMOUS VEHICLES - Lucie VONDRÁČKOVÁ; Martina TREPÁČOVÁ; Petr ZÁMEČNÍK (Transport Problems, 2022)
In a few years, autonomous vehicles will slowly become part of traffic flow. This paper evaluated the level of perceived fear of interactions of autonomous vehicles (AVs) with other (vulnerable) road users of different actors in the Czech Republic. Data from the first exploratory project from 2017/2018 are used for the evaluation. A logistic regression model is utilised to evaluate the predictors that influence the fear resulting from interactions of AVs and cyclists or pedestrians. Kilometres driven last year was positively associated with fear of interactions with pedestrians or cyclists (OR = 1,251, p = 0.032). The level of concerns about the risk of AVs is also positively associated with fear of interactions (OR = 1.087, p = 0.000). Out of all socio- demographics and socio-economics, only gender was distinguished regarding the level of fear, with women having a higher chance than men of being fearful (OR = 1.871, p = 0.005). Then, the same model is utilised to evaluate the variables that influence the fear of interactions of Avs and other non-Avs. Only the general level of concerns about the risk of AVs is associated with the level of fear of interactions of AVs and non-AVs (OR = 1.149, p = 0.000). Since these results are only partly in accordance with those obtained in Western countries, our paper concludes that for central European countries, more research is needed to understand the local context and implications of autonomous mobility.